Six new species of spider beetles (Coleoptera: Ptinidae) in the genus Cordielytrum Philips - Whorrall, Kyle; Philips, Keith (Zootaxa, 2021)
Six new species of spider beetle are described from southwestern Peru: Cordielytrum silvae, sp. n., C. inca, sp. n., C. fimbriatum, sp. n., C. obscurum, sp. n., C. adustum, sp. n., and C. globuloides, sp. n. The potential for undescribed diversity in this genus is discussed, as well as the geographic distribution and biology of species.